Pengembangan UMKM Kripik Pisang Sebagai Penopang Ekonomi Desa Anggaloosi - Nartin N (Yayasan Daarul Huda Kruengmane, 2026)
This Community Service Program (KKN) was conducted in Anggaloosi Village with the aim of supporting the development of banana chips Micro, Small, and Medium Enterprises (MSMEs) as an effort to improve the village's economic condition. The activity was driven by the significant potential of banana agriculture in the village, which had not been fully utilized. Through a participatory approach, the KKN team provided assistance in various aspects including banana chips production training, product packaging, marketing strategies, and business financial management. The results showed an increase in the community's knowledge and skills in managing banana chip businesses more professionally. It is expected that this MSME initiative will become a sustainable economic pillar of the village and create employment opportunities for local residents.